The Regulation of Apoptosis in Kidney Development: Implications for Nephron Number and Pattern? - Ho, Jacqueline (Frontiers in Pediatrics, 2014)
Apoptosis is essential to remodel developing structures and eliminate superfluous cells in a controlled manner during normal development, and continues to be an important component of tissue remodeling and regeneration during an organism’s lifespan, or as a response to injury. This mini review will discuss recent studies that have provided insights into the roles of apoptosis in the determination of nephron number and pattern, during normal and abnormal kidney development. The regulation of congenital nephron endowment has implications for risk of chronic kidney disease in later life, whereas abnormalities in nephron pattern are associated with congenital anomalies of the kidney and urinary tract (the leading cause of renal disease in children). Tight regulation of apoptosis is required in normal renal morphogenesis, although many questions remain regarding the regulation of apoptosis by genetic, epigenetic, and environmental factors, in addition to the functional requirement of different components of the apoptotic pathway.